Uma correnteza que conduz aos fluxos vivos da memória: a criação em farejos de um tempo roubado - Ferreira, Lara Xerez Peixoto (2024)
A dive into orí, a dive into what can be imagined. Stolen time is a constant flow sniffing out memories that were buried by coloniality. Memories that endure in the quilombo experience, in orality and in Afro-Brazilian culture. Weaving dialogues with Beatriz Nascimento, Grada Kilomba, Leda Maria Martins and Muniz Sodré, I elaborate on the conceptions about memory for the black Brazilian population, relating them to my life memories. Elaborating propositions about the currents of ancestry, with Sandra Pétit, Nego Bispo, Jaider Esbell and Pedra Silva. Flowing in the rivers that find paths, I share performative actions carried out between the years 2020 and 2022 that make up the paths of resuming paths and imagination. Starting from the poetic relationship between word and body, creation takes place in spaces of natural strength, rivers, beaches, mangroves, crossing ancestral spaces and territories.